2012
DOI: 10.1111/j.1748-0361.2012.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Living in Rural and Urban Areas: Vitamin D and Medical Costs in Veterans

Abstract: Purpose: Living in a rural region is associated with significant health disparities and increased medical costs. Vitamin D deficiency, which is increasingly common, is also associated with many adverse health outcomes. The purpose of this study was to determine whether rural‐urban residence status of veterans was related to vitamin D levels, and to determine if this factor also influenced medical costs/service utilization. Additionally explored was whether vitamin D differences accounted for part of the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
3
12
1
Order By: Relevance
“…One study of over Mexican children found higher 25 [28]. Indeed, all areas had an average 25(OH)D concentration of 28-30nmol/L [28]. Similarly, in an Indian study [29] and a study in the United Kingdom (UK) [30], no difference in 25(OH)D concentrations between residents of urban or rural areas was identified.…”
Section: Examination Of Data From the Korean National Health And Nutrmentioning
confidence: 96%
See 1 more Smart Citation
“…One study of over Mexican children found higher 25 [28]. Indeed, all areas had an average 25(OH)D concentration of 28-30nmol/L [28]. Similarly, in an Indian study [29] and a study in the United Kingdom (UK) [30], no difference in 25(OH)D concentrations between residents of urban or rural areas was identified.…”
Section: Examination Of Data From the Korean National Health And Nutrmentioning
confidence: 96%
“…One study of over Mexican children found higher 25 [28]. Indeed, all areas had an average 25(OH)D concentration of 28-30nmol/L [28].…”
Section: Examination Of Data From the Korean National Health And Nutrmentioning
confidence: 98%
“…As the skin synthesis of vitamin D, which occurs through the action of sunlight, is not surprising that a reduced radiation caused by air pollution constitutes one of the main causes of vitamin D deficiency [4]. Accordingly, urban residents, especially in areas with high levels of ambient air pollution, tend to be less engaged in outdoor activities and have a higher prevalence of D hypovitaminosis compared to rural inhabitants [7]. …”
Section: Air Pollution and Low Vitamin D Statusmentioning
confidence: 99%
“…In fact, urban residence itself might be a major determinant of vitamin D status among the homeless. However, American studies have shown better vitamin D status for urban residents than for rural residents [24,25]. Other behavior and cultural factors, not evaluated in this study, could also affect vitamin D status.…”
Section: Discussionmentioning
confidence: 73%